2013
DOI: 10.1099/vir.0.051052-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Favourable’ IL28B polymorphisms are associated with a marked increase in baseline viral load in hepatitis C virus subtype 3a infection and do not predict a sustained virological response after 24 weeks of therapy

Abstract: 'Favourable' IL28B polymorphisms are associated with a marked increase in baseline viral load in hepatitis C virus subtype 3a infection and do not predict a sustained virological response after 24 weeks of therapy IL28B host genetic make-up is known to play a critical role in the outcome of genotype 1 hepatitis C virus (HCV) infection in the context of both primary infection and therapy. However, the role of IL28B in subtype 3a infection remains unclear, and has not yet been assessed in the UK population where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…20,25 In our cohort even though the relapse rate was as high as 20% ( Table 3) there was no association of rs8099917 with relapse (p=0.420). These results suggest that similar to SNP with both RVR and SVR.…”
Section: Genotypes At Rs8099917 Do Not Significantly Associate With Rmentioning
confidence: 94%
See 3 more Smart Citations
“…20,25 In our cohort even though the relapse rate was as high as 20% ( Table 3) there was no association of rs8099917 with relapse (p=0.420). These results suggest that similar to SNP with both RVR and SVR.…”
Section: Genotypes At Rs8099917 Do Not Significantly Associate With Rmentioning
confidence: 94%
“…Several studies have shown association of IL28B SNPs with RVR in genotype 3 HCV infections, but no significant association has been seen with SVR. 20,24,25 Mangia et al from Italy genotyped ~300 chronic HCV genotype 2/3 infected patients who received standard combination therapy. They were tested for associationsbetween rs12979860 genotypes and RVR and SVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral genotype is emerging as a central determinant of whether the above polymorphisms can exert any influence on viral clearance; for example variants of IFN‐λ3/4 play a limited role in predicting HCV related outcomes in patients infected with HCV G2/3 23. Recent work has suggested this may be a result of genotype 1 viral infection inducing transcripts which are heavily regulated by IFN‐λ3/4, whereas HCV G2/3 infection leads to the upregulation of genes induced by IFN‐γ 24.…”
Section: Introductionmentioning
confidence: 99%